BRIDGING THERAPY RESULTS IN PATIENTS WITH ACUTE CALCULOUS CHOLECYSTITIS AND CONCOMITANT ISCHEMIC HEART DISEASE - Dinets , A.V.; Kondratenko , S.O.; Markulan , L.Yu.; Holinko , V.M. (The Ukrainian Scientific Medical Youth Journal, 2018)
Introduction. Binding or bridging therapy (BT) suggests long-term administration of short acting anticoagulants (unfractionated heparin – UFH or low-molecular-weight heparin – LMWH) during preoperative preparation and early postoperative period in patients who had been receiving anticoagulation therapy (ACT) or anti-aggregation therapy (AAT) for a long time before surgery. The generalized data on the BT technique for urgent surgical interventions, particularly, in patients with acute calculous cholecystitis (ACH) and concomitant ischemic heart disease (IHD), is currently lacking. The aim of the work – to improve the BT technique in patients with ACH and IHD and to evaluate the results of its application.Materials and methods. The study included 73 patients– 33 (45,2 %) women and 40 (54,8 %) men aged 57 to 81 years, on average 71,4 ± 0,7 years, who had received ACT or AAT before the hospitalization. All patients were admitted to hospital within 72 hours (from 6 to 65 hours) from the onset of the disease, on average 27.3 ± 1.5 hours. The catarrhal ACH occurred in 27 (37,0%) patients, phlegmonous – in 21 (28,8 %) patients, gangrenous – in 25 (34,2 %) patients. According to Tokyo Guidelines for the management of acute cholangitis and cholecystitis (TG13), 19 (26.0 %) patients had ACH I degree, 31 (42.5 %) patients– ACH II degree, 23 (31.5 %) patients – ACH III degree. There were 3 (4.1 %) patients with NYHA class I heart failure, 39 (53.4 %) patients with NYHA class II heart failure, 26 (35.6 %) patients with NYHA class III heart failure, and 5 (6.8 %) patients with NYHA class IV heart failure. The advanced tactics of bridging therapy was applied, which depended on several factors such as INR, aPTT, creatinine clearance, Lee-White’s bleeding time. The target points were the frequency of INR or bleeding time therapeutic range achieving, and the frequency of hemorrhagic complications.Results and discussion. Immediately before surgery (laparoscopic cholecystectomy), the target (therapeutic) INR range >2 was obtained in 18 (90 %) patients among 20 patients who had previously received warfarin. Among them 2 (10.0 %) patients had INR in the range of 1.3-2.0, 12 (60.0%) patients had INR in the range of 2.1-3.0, and 6 (30.0 %) had INR >3.1. The target value of bleeding time >12 min was in 48 (90.6 %) patients among the patients (53 patients) who had received AAT earlier. The values of bleeding time in the range of 10-12 min were in 5 (9.4 %) patients, 12.1-14 min –in 42 (79.2 %) patients, >14 min – in 6 (11.3 %) patients. In general, INR and bleeding time values were within the therapeutic window in 65 (90.3 %) patients, and there was no patient with signs of hypercoagulation. In the postoperative period, the dynamics of INR and bleeding time values were similar and figured out at increase in the part of patients with INR 2.1-3.0 and bleeding time 12.1-14 min respectively.